Reduction of noise in the neonatal intensive care unit using sound-activated noise meters. Issue 6 (25th August 2014) - Wang, D; Aubertin, C; Barrowman, N; Moreau, K; Dunn, S; Harrold, J
Abstract : Objectives: To determine if sound-activated noise meters providing direct audit and visual feedback can reduce sound levels in a level 3 neonatal intensive care unit (NICU). Design/methods: Sound levels (in dB) were compared between a 2-month period with noise meters present but without visual signal fluctuation and a subsequent 2 months with the noise meters providing direct audit and visual feedback. Results: There was a significant increase in the percentage of time the sound level in the NICU was below 50 dB across all patient care areas (9.9%, 8.9% and 7.3%). This improvement was not observed in the desk area where there are no admitted patients. There was no change in the percentage of time the NICU was below 45 or 55 dB. Conclusions: Sound-activated noise meters seem effective in reducing sound levels in patient care areas. Conversations may have moved to non-patient care areas preventing a similar change there.